2008
DOI: 10.1080/02757540802119889
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase activity in rats exposed to methyl parathion

Abstract: Methyl parathion is an organophosphate insecticide that has been used in agriculture and the domestic sector for several years. This pesticide and others, arriving through different processes, exert significant effects on water quality with serious consequences for environmental and human health. The main objective of this study was to investigate the changes of Glutathione S-transferase enzyme activity in methyl parathion exposed rat tissues. For this purpose, wistar rats (Rattus norvegicus) were injected int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In addition, chronic exposure of rats and mice to pesticide led to increased levels of serum ALT and AST (Gomes et al, 1999). Our present data, in agreement with those from a previous study, found that dinitro-o-cresol, dichlorvos, and methyl parathion, which are all used as pesticides, caused increases and decreases in serum enzyme activities and some biochemical parameters in female and male rats (Dere et al 2007;Ozdikicioglu et al, 2008;Ari and Dere, 2008). Our present data, in agreement with those from a previous study, found that dinitro-o-cresol, dichlorvos, and methyl parathion, which are all used as pesticides, caused increases and decreases in serum enzyme activities and some biochemical parameters in female and male rats (Dere et al 2007;Ozdikicioglu et al, 2008;Ari and Dere, 2008).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, chronic exposure of rats and mice to pesticide led to increased levels of serum ALT and AST (Gomes et al, 1999). Our present data, in agreement with those from a previous study, found that dinitro-o-cresol, dichlorvos, and methyl parathion, which are all used as pesticides, caused increases and decreases in serum enzyme activities and some biochemical parameters in female and male rats (Dere et al 2007;Ozdikicioglu et al, 2008;Ari and Dere, 2008). Our present data, in agreement with those from a previous study, found that dinitro-o-cresol, dichlorvos, and methyl parathion, which are all used as pesticides, caused increases and decreases in serum enzyme activities and some biochemical parameters in female and male rats (Dere et al 2007;Ozdikicioglu et al, 2008;Ari and Dere, 2008).…”
Section: Resultssupporting
confidence: 92%
“…
Fenarimol,a 2, benzhydryl alcohol fungicide and steroid demethylation inhibitor, has been reported to affect the actions of multiple CYP450 isoforms, including key enzymes. The aim of this study was to evaluate the effects of fenarimol on a set of biochemical parameters in rats.
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To understand whether pesticides affect non-target organisms, enzyme activities in damaged tissues can be examined [28][29][30][31][32]. Although there are studies on the GST activity of pesticides in the literature [33][34][35][36], there is no study on the GST activity of fenarimol in rat tissues. Therefore, it is important to know the effect of fenarimol on rats.…”
Section: Discussionmentioning
confidence: 99%